Diurnal Blood Pressure Abnormalities Are Related to Endothelial Dysfunction in Patients with Non-Complicated Type 1 Diabetes - YAVUZ, DİLEK; YÜKSEL, MERAL (NATURE PUBLISHING GROUP, 2008)
Patients with diabetes have an increased cardiovascular morbidity and mortality despite interventions to prevent these outcomes. Abnormalities in diurnal blood pressure patterns are also associated with excess cardiovascular mortality. The aim of this study was to determine the effects of diurnal blood pressure patterns on endothelial function and oxidative stress in patients with uncomplicated type 1 diabetes mellitus. Thirty-two normotensive and normoalbuminuric type 1 diabetic patients (21 dipper and 11 nondipper) and 37 healthy (27 dipper and 10 nondipper) volunteers underwent 24-h ambulatory blood pressure monitoring. Their endothelial functions were evaluated using flow mediated dilatation (FMD) and by measuring nitric oxide and thiobarbituric acid reactive substances (TBARS). Dippers were defined as subjects who exhibited an average reduction in both systolic and diastolic blood pressure of greater than 10% between day and night periods. Nondipper type 1 diabetic patients and controls had nighttime systolic and diastolic blood pressure values that were significantly higher than those of dipper diabetic patients (p<0.05) and dipper controls (p<0.01). Values of FMD for nondipper diabetic patients (5.12 +/- 2.2%) were significantly lower than those In dipper diabetic patients (10.19 +/- 2.5%, p<0.01), nondipper (10.08 +/- 2.9%, p<0.001) and dipper controls (11.76 +/- 0.8%, p<0.001). Additionally, levels of TBARS In the dipper diabetic group and dipper controls were significantly lower than those in the nondipper diabetic group (p<0.05). In conclusion, only type 1 diabetic patients with a nondipping pattern of blood pressure exhibited changes that may lead to endothelial dysfunction and atherosclerosis. (Hypertens Res 2008; 31: 2065-2073)
Keywords: ambulatory blood pressure monitoring; endothelial function; diabetes; nondipper; oxidative stress; BLUNTED NOCTURNAL FALL; 6-YEAR FOLLOW-UP; ESSENTIAL-HYPERTENSION; AUTONOMIC NEUROPATHY; DEPENDENT VASODILATION; OXIDATIVE STRESS; IDDM PATIENTS; MORTALITY; MELLITUS; DISEASE